Biostratigraphy of the Late Miocene Halang Formation in the Loh Pasir Succession, Banyumas, Central Java - Marfasran Hendrizan; Rubiyanto Kapid; Djuhaeni Djuhaeni (Ikatan Ahli Geologi Indonesia, 2014)
A detailed biostratigraphic study was conducted to determine the spatial and temporal relationships between the Miocene Halang and Pemali Formations in Central Java. We studied calcareous nannofossils from a 1.4 km thick outcrop section of the Halang Formation at Loh Pasir to document biostratigraphic changes in the Banyumas area. The marine Halang Formation shows three types of lithofacies, predominantly mixed sandy and muddy in the upper part and muddy and sandstone facies in the lower part. We identified 57 species of 13 genera of calcareous nannofossils in 121 samples, which could be divided into five Late Miocene biozones. These zones are Discoaster brouweri, Discoaster hamatus, Discoaster bollii, Discoaster prepentaradiatus and Discoaster quinqueramus. Our results are consistent with previous biostratigraphic work in the Karanggedang 1 well location, except in the lower part of this formation, due to the lack of Catinaster coalitus in the Loh Pasir section.